Houdini's box : on the arts of escape / Adam Phillips. - Phillips, Adam (Faber, 2001)
In this book, Adam Phillips helps us understand why we feel most alive in the very moment of escape. Previous titles by the author include On Kissing, Tickling and Being Bored, Monogamy and Promises, Promises.